Investigating Respect in Learning as Character Education: A Review of al-Zarnūjī’s Ta‘līm al-Muta‘allim - Huda, Miftachul; Selamat, Abu Zarrin; Salem, Sultan (Nazhruna: Jurnal Pendidikan Islam, 2024)
Respect has been shown to provide psychological, social, and academic advantages; nevertheless, most academics have not given it enough credit in terms of encouraging students’ character development. Al-Zarnūjī’s idea, a classical Muslim scholar, as a point of reference for his esteemed work on the concept of Ta‘līm al-Muta‘allim has been one of the references in learning and teaching guidelines among pesantren (Islamic boarding schools) in Indonesia. This article aims to critically explore respect as a moral concept and explain how respect can contribute to current discussions in developing character education from the perspective of al-Zarnūjī’s Ta‘līm al-Muta‘allim. A critical analysis of books and journals that were cited was done concerning the contributions made in the field of character education. The study’s findings have led to three major disputes. The first is deference to knowledge as a source of illumination. Secondly, it is deference to the instructor as the foremost exemplar and facilitator of information exchange; and thirdly, it is honoring the colleague as a fellow participant in the educational journey. Respect in all of its dimensions should thus guide the process of teaching and learning.